2012
DOI: 10.2174/092986612803217114
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Microwave-Assisted Solid-Phase Peptide Synthesis Using Fmoc Strategy: In-Water Synthesis of "Difficult Sequences"

Abstract: A microwave assisted peptide synthesis in water using nanosized Fmoc-amino acids was developed. 5, 7, and 10 mer peptides (Leu-enkephalinamide, dermorphinamide, and a typical difficult sequence, ACP (65-74) peptide) were successfully synthesized in water according to Fmoc chemistry using water-dispersible nanoparticles with microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In the previous work using Fmoc-amino acid nanoparticles, we have studied about efficiency of these aqueous MW-assisted coupling conditions. Even when using Fmoc amino acid nanoparticles, DMTMM showed a high reactivity in the aqueous reaction with MW irradiation [24]. These results were suggested that the microwave radiation in highly polar water-based solvent systems leads to very smooth reactions between aqueous nanoparticles and the solid support.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the previous work using Fmoc-amino acid nanoparticles, we have studied about efficiency of these aqueous MW-assisted coupling conditions. Even when using Fmoc amino acid nanoparticles, DMTMM showed a high reactivity in the aqueous reaction with MW irradiation [24]. These results were suggested that the microwave radiation in highly polar water-based solvent systems leads to very smooth reactions between aqueous nanoparticles and the solid support.…”
Section: Resultsmentioning
confidence: 97%
“…We also successfully prepared water-dispersible Boc-Tyr(BrZ)-OH, which has a hydrophobic BrZ side chain protecting group [11]. WSCI [31], DMTMM [32,33] and combinations of an additive sulfo-HOSu [34] were examined [24]. Reaction temperature was 70 °C using a MW power of 70 W (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of synthesis methods that do not use organic solvents would be desirable (Anastas and Warner 1998;Winterton 2001;Sheldon 2007). In recent years, we have been driven to focus on the development of a method for peptide synthesis in water which is an environmentally friendly solvent (Hojo et al 2001(Hojo et al , 2004a(Hojo et al , b, 2007(Hojo et al , 2008(Hojo et al , 2011(Hojo et al , 2012(Hojo et al , 2013. Solid-phase peptide synthesis (SPPS) is commonly performed via a base-labile 9-fluorenylmethoxycarbonyl (Fmoc) strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, Fmoc-amino acids are sparingly soluble in water and have been considered inappropriate for in-water peptide synthesis. With the aim of achieving aqueous SPPS, we developed in-water synthesis protocols using water-dispersible nanoparticulate Fmoc-amino acids (Hojo et al 2007(Hojo et al , 2008(Hojo et al , 2011(Hojo et al , 2012(Hojo et al , 2013. This technology uses suspended nanoparticle reactants for the coupling reaction to overcome the solubility problem.…”
Section: Introductionmentioning
confidence: 99%